PENGARUH KINERJA PERUSAHAAN TERHADAP HARGA SAHAM SEKTOR PERDAGANGAN, JASA DAN INVESTASI YANG TERDAFTAR DI ISSI PERIODE 2012-2017 - Armeita Maya Shanty; Ari Prasetyo (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
This research aims to determine the effect of current ratio, total asset turnover, return on assets, debt to equity ratio, and earnings per share partially or simultaneously to stock prices of trade, services and investment sectors registered in ISSI for period 2012-2017. This research uses quantitative approach by using secondary data in the form of financial statements of stock of trading sector price, services dan investments registered in the ISSI in year 2012-2017. Regression result by using technique of panel data analysis with Eviews 10. The results of this study indicate that simultaneously variable of current ratio, total assets turn over, return on asset, debt to equity ratio, and earnings per share have significant effect to stock price of trading sector, services and investment registered in ISSI. Partially variable of current ratiohave positive and significant influence, total assets turn over have negative influence and not significant, return on asset have positive and significant influence, debt to equity ratio have negative and significant effect, earning per share have positive and significant effect to stock of trading sector price , services and investments registered in the ISSI period 2012-2017.  REFERENCESAnoraga, Panji dan Piji Pakarti. 2001. Pengantar Pasar Modal. Edisi revisi.    Rineka Cipta. Semarang.Anshori, Mucslich dan Sri Iswati. 2009. Metodologi Penelitian Kuantitatif. Surabaya: Pusat Penerbitan dan Percetakan UNAIR.Brigham dan Houston. 2010. Dasar-dasar Manajemen Keuangan Buku 1 (Edisi 11). Jakarta : Salemba Empat.Bursa efek Indonesia, online, http://www.idx.co.id.Departemen Agama RI. 2012. Al-Quran dan Terjemahannya Revisi Tahun 2012. Jakarta: DEPAG RI.Darmadji, Tjiptono dan Hendy M. Fakhrudin. 2011. Pasar Modal di Indonesia Edisi 3. Jakarta: Salemba Empat.Ghozali, Imam. 2011. Aplikasi Analisis Multivariate dengan Program IBM  SPSS19, Badan Penerbit Universitas Diponegoro, Semarang.Gujarati, Damodar. 2003. Basic Econometric. New York: The McGraw-Hill Companies,Inc. -------------. 2013. Ekonometrika Dasar Buku 2. New York: The McGraw- Hill Companies, Inc. Hidayat, Taufik. 2011. Buku Pintar Investasi Syariah. Jakarta : PT TransMedia.Otoritas jasa keuangan, online, http://www.idx.co.id.Quthb, Sayyid. 2004. Tafsir Fi Zhilalil Qur’an. Jakarta: Gema InsaniSofyan Syafri Harahap. (2011). Analisis Kritis Atas Laporan Keuangan. Jakarta: Raja grafindo Persada.Sutedi, Adrian. 2014. Pasar Modal Syariah. Jakarta. Sinar Grafika Syamsuddin, 2009. Manajemen Keuangan Perusahaan. Jakarta: PT. Raja Grafindo PersadaWidarjono, Agus. 2005. Ekonometrika : Teori dan Aplikasi untuk Ekonomi dan Bisnis. Edisi Kedua. Yogyakrta : Ekonosia Fakultas Ekonomi UII.